A magnesium–sodium hybrid battery with high operating voltage. Issue 53 (10th June 2016) - Dong, Hui; Li, Yifei; Liang, Yanliang; Li, Guosheng; Sun, Cheng-Jun; Ren, Yang; Lu, Yuhao; Yao, Yan
Abstract : A low-cost high-power Mg–Na hybrid battery enabled by high-voltage Mg–Na dual salt electrolyte, open framework cathode, and the fast-kinetic Mg metal anode is demonstrated. Abstract : We report a high performance magnesium–sodium hybrid battery utilizing a magnesium–sodium dual-salt electrolyte, a magnesium anode, and a Berlin green cathode. The cell delivers an average discharge voltage of 2.2 V and a reversible capacity of 143 mA h g −1 . We also demonstrate the cell with an energy density of 135 W h kg −1 and a high power density of up to 1.67 kW kg −1 .